The Use of Wordwall Application Towards Elementary School Students Acceptance: Extension TAM Model - Elsa Ananda Putri; Zulherman Zulherman (AL-ISHLAH: Jurnal Pendidikan, 2022)
This research aims to prove elementary school students' interest in the adoption use of the Wordwall as a game-based learning application, which is directly proportional to the concept of learning gamification, by proposing a solution to make an interactive activity using Edu-games-based teaching materials that can be implemented with learning activities during pandemic Covid-19. This research expands TAM (Technology Acceptance Model) basic theory by adding external variables of perceived enjoyment and habit by employing a survey method and taking a sample of elementary school students, as many as 90 students, to analyze the elementary school students' interest using the Wordwall application in learning with the concept of gamification. The data is processed using SEMPLS to see the results of the tested independent variables. TAM model adopted in this study has succeeded in achieving interrelated prediction, this research indicates that perceived enjoyment and habit become the influencing factor in increasing Wordwall usage interest through key variables (PEOU), that is, the perceived ease of using the application as the most strengthen and effective key variable in this research. This study also focuses on the proposed model contribution with the final review, which impacts the proposed hypothesis predictions through the technology acceptance by elementary school students in using a game-based learning platform digital.